# How do you solve (3y + 2) = ( 4y - 3)?

Nov 13, 2017

$y = 5$

#### Explanation:

color(blue)((3y+2)=(4y-3)

First of all, take of the parenthesis

$\rightarrow 3 y + 2 = 4 y - 3$

Add $3$ both sides

rarr3y+2+color(red)(3)=4ycancel(-3+color(red)(3)

$\rightarrow 3 y + 5 = 4 y$

Subtract $3 y$ both sides

$\rightarrow \cancel{3 y} + 5 - \cancel{\textcolor{red}{3 y}} = 4 y - \textcolor{red}{3 y}$

$\rightarrow 5 = y$

color(green)(rArry=5

Hope that helps!!! ☺☻

Nov 13, 2017

See a solution process below:

#### Explanation:

First, remove each term from their parenthesis;

$3 y + 2 = 4 y - 3$

Next, subtract $\textcolor{red}{3 y}$ and add $\textcolor{b l u e}{3}$ to each side of the equation to solve for $y$ while keeping the equation balanced:

$- \textcolor{red}{3 y} + 3 y + 2 + \textcolor{b l u e}{3} = - \textcolor{red}{3 y} + 4 y - 3 + \textcolor{b l u e}{3}$

$0 + 5 = \left(- \textcolor{red}{3} + 4\right) y - 0$

$5 = 1 y$

$5 = y$

$y = 5$

Jan 10, 2018

See below

#### Explanation:

Usually i don't consider increasing my workin by subtracting something from both sides . I decrease the work by shifting variables and constants from L.H.S to R.H.S or vice-versa .
$3 y + 2 = 4 y - 3$
I took 3y to R.H.S and -3 to L.H.S by inverting their additive signs .
This becomes
$2 + 3 = 4 y - 3 y$
$5 = y$ .